Comparison of Membrane Protein Glycopeptides of Sindbis Virus and Vesicular Stomatitis Virus - Burge, Boyce W. (1970)
A comparison has been made of the membrane glycoproteins and glycopeptides from two enveloped viruses, Sindbis virus and vesicular stomatitis virus (VSV). Glycopeptides isolated from Sindbis virus and VSV grown in the same host appear to differ principally in the number of sialic acid residues per glycopeptide; when sialic acid is removed by mild acid treatment, the glycopeptides of the two viral proteins are indistinguishable by exclusion chromatography. Preliminary evidence argues that the carbohydrate moiety covalently bound to different virus-specified membrane proteins may be specified principally by the host.